Tendências da mortalidade por câncer de pênis no estado do Pará segundo o período de 1996 a 2005 - MOREIRA FILHO, Oberdã Gomes (2022)
The penile cancer has a variable incidence according to the geographic region, but it is still worrying in countries of the Latin America, Africa and Asia. The mortality happens generally on advanced stages, being associated to delay at the find of medical attention and to a bigger exposition to risk factors, like phimosis, uncircumcision, smoking, poor hygiene, low social and economic levels, high number of sexual partners, besides repeated penile trauma history. The objectives of this search were to analyze the penile cancer mortality standard coefficient tendencies, according to the big region of the state of Para from 1996 till 2005; to identify unequal tendencies and situations that can demand specials studies; subsidize planning processes, political management and evaluation and preventive and assistant actions related to penile cancer; to contribute in health levels and social and economic people development. The mortality rates were taken from the Death Declarations from the Mortality Information System of Ministry of Health, supplied by Pará Public Health of State Executive Secretariat; the people rates were taken from demographic census of the year 2000. Penile cancer mortality brute rates were calculated to the state of Para and its regions to periods of two years (1996-1997; 1998-1999; 2000-2001; 2002-2003; 2004-2005), objecting reduce possible temporaries variations. The information base was extracted from the epidemiologic software EPIINFO 6.01b version, from where simple descriptive statistics will be obtained with an application of statistics tests (Qui-square) to the measure of the find results. The metropolitan region presented standard penile cancer mortality rates between 0.70 and 1.39/100000 and Para between 0.32 and 0.54/100000, being observed an increase rates tendency in the analyzed period. The mortality rates showed an increase directly proportional to the age, being higher in people oldest than 80 years old (41.84/100000). The standard penile cancer mortality rates present important differences between the capital and countries of the state, varying between 3 and 16 times.